Effect of receptor protein kinase inhibition on the morphogenesis of experimental diabetic retinopathy (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the effect of receptor protein kinase inhibition with the multi-target kinase inhibitor sorafenib on the morphogenesis of experimental diabetic retinopathy (DR).Material and Methods: Type 1 diabetes mellitus (DM) was induced in 60 Wistar male rats (age, 3 months) by single intraperitoneal injection of streptozotocin (STZ; Sigma-Aldrich, China) at a dose of 50 mg/kg body weight. Rats were divided into 3 groups 20 rats each: group 1 or controls (no treatment), group 2 (30 units of insulin only (Novo Nordisk A/S, Bagsvaerd, Denmark) every other day), and group 3 (insulin combined with soranib (sorafenib, Сipla, India), 50 µg/kg body weight daily). Five intact rats were used to determine baseline parameters. Rats were euthanized on days 7, 14, 28 and month 3. Paraffin retinal sections were stained with hematoxylin and eosin or AZAN trichrome (BIOGNOST Ltd, Croatia) and visualized by light microscopy.Results: On day 7 after STZ injection, general signs of diabetic damage to the retina (vascular abnormalities, retinal edema and ischemic areas) were observed. Specific signs of DR (microaneurysms along the inner retinal surface, ganglion cell degeneration, reactive gliosis, cell proliferation in the outer retinal layers and an increased inner limiting membrane thickness with accumulation of coarse basophilic fibers) manifested subsequently in the course of experimental type 1 DM. Insulin-only treatment contributed to a reduction in all manifestations of diabetic damage to the retina, whereas application of sorafenib as an adjunct to treatment reduced general signs and prevented specific manifestations of DR.Conclusion: Inhibition of cellular protein kinases made it possible to prevent signs of DR, which prompts further research on opportunities for application of this approach in the treatment of DR.
Keywords: diabetic retinopathy; streptozotocin; microaneurysms; retinal degeneration; gliosis; insulin